Pengembangan Sistem Informasi Review Smartphone Studi Pada TNT Cell Bojonegoro - Aulia Septi Pertiwi; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
88% smartphone users read reviews about smartphone. Smartphone reviews can be found on various websites. TNT Cell is one of the mobile counter that sells various brands of smartphone. One of business process at TNT Cell is the consultation process about smartphone, some of the customers can't understand well about the advantages and disadvantages of smartphone, although it has been explained by the officer. That case will affects the process of customer decision making. Based on these problems an information system about smartphone review was developed. This system will give the customer information about smartphones by review from several websites and conducting sentiment analysis on reviews. Web scraping methods are used in this system to extract reviews from sites priceprice.com, pricebook.co.id, and iprice.co.id. In the process of sentiment analysis, one of the classification methods that used was Support Vector Machine. The software development method that used in this research is the waterfall model method. The testing technique that used on this research are validation testing, compatibility testing, and usability testing. The result of validation testing is all of the given test case are valid, that mean the system has been built appropriate with the user requirement.